2011
DOI: 10.4067/s0718-58392011000100004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ethephon on Almond Bloom Delay, Yield, and Nut Quality under Warm Climate Conditions in Northwestern Mexico

Abstract: World almond (Prunus dulcis (Mill.) D.A. Webb) production is mostly located in areas where flowering is injured by low temperatures, and using ethephon (2-chloroethylphosphonic acid) to delay bloom is suggested as a measure to avoid frost damage. However, it is unknown if that practice could be beneficial in Mexico's warm climates. The objective of this study was to determine the effect of ethephon on almond bloom delay and yield. We evaluated foliar applications of ethephon at doses of 75, 150, and 300 mg L -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…These effects of the chemicals lead to limited energy production and transfer (Polat et al, 2017). This affects the duration of plastochron and prolongs the time needed by flower buds to open (Krewer et al, 2005;Grijalva-Contreras et al, 2011;Wang et al, 2014). In the current study, the single application of mepiquat chloride during the dormant period delayed blooming up to 8 days, while the single ethephon treatment yielded a delay in blooming up to 10 days (Figure 1).…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…These effects of the chemicals lead to limited energy production and transfer (Polat et al, 2017). This affects the duration of plastochron and prolongs the time needed by flower buds to open (Krewer et al, 2005;Grijalva-Contreras et al, 2011;Wang et al, 2014). In the current study, the single application of mepiquat chloride during the dormant period delayed blooming up to 8 days, while the single ethephon treatment yielded a delay in blooming up to 10 days (Figure 1).…”
Section: Resultsmentioning
confidence: 51%
“…In the current study, the single application of mepiquat chloride during the dormant period delayed blooming up to 8 days, while the single ethephon treatment yielded a delay in blooming up to 10 days (Figure 1). The studies on delay of blooming using ethephon have shown that blooming was delayed by 5 to 9 days in peach trees depending on the year (Crisosto et al, 1989), 1 to 3 days in cherry trees depending on the cultivar (Engin et al, 2004), 4 to 11 days in Japanese apricot (Paksasorn et al, 1995), 12 to 15 days in pistachio (Askari et al, 2011), 5 to 7 days in cranberry (Krewer et al, 2005), 17 to 30 days in Physalis (Yadava, 2012), and 2 to 9 days in almond (Grijalva-Contreras et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…For example, when applied at 10% leaf drop, 250 and 500 ppm ethephon delayed bloom in plums (Prunus domestica) by 13 and 16 days, respectively; whereas only 5 and 7 days bloom delay was observed when ethephon was applied at 50% leaf drop stage (Crisosto et al, 1990). The effectiveness of ethephon appears to be limited to the pre-dormancy stage, as serious flower bud abscission was induced when application was made after the satisfaction of CR (Durner and Gianfagna, 1991), and little or no effect was found when ethephon was applied in apricot during the dormancy stage (Grijalva-Contreras et al, 2011). In addition to delaying bloom date, fall application of ethephon was also found to enhance cold hardiness of dormant buds.…”
Section: Ethylene As a Bloom-delaying Agentmentioning
confidence: 99%
“…Despite the significant success in using ethephon to delay bloom and prevent spring frost, some studies have indicated beneficial effects of ethephon can be comprised by the occurrence of detrimental effects such as gummosis, leaf yellowing and abscission, terminal dieback, flower abscission, floral bud failure, low fruit set, and yield reduction ( Table 1 ). Furthermore, fall application of 75–300 ppm ethephon on almond caused up to 3-fold yield reduction, and the yield reduction was in proportion to the ethephon concentrations (Grijalva-Contreras et al, 2011). Such linear yield decrease caused by increasing ethephon concentrations was also documented in peach (Crisosto et al, 1990).…”
Section: Limitations Of Using Ethylene In Delaying Bloommentioning
confidence: 99%
See 1 more Smart Citation